The effectiveness of the project-based learning model with the STEAM approach in the woodworking practice course - Fani Keprila Prima; Rijal Abdullah; Juniman Silalahi; Ari Syaiful Rahman Arifin; Trimailuzi Trimailuzi (Jurnal Pendidikan Teknologi Kejuruan, 2026)
The transformation of vocational education requires learning models that not only emphasize project completion but also ensure product quality aligned with industry standards. This study investigates the effectiveness of integrating Project-Based Learning (PjBL) with a STEAM approach and inspection-based Quality Control (QC) in enhancing student competencies in a Woodworking Practice course. A quasi-experimental design with a non-equivalent control group was employed. The experimental group experienced PjBL–STEAM integrated with three stages of inspection-based QC (incoming, in-process, and final inspection), while the control group received conventional instruction without systematic QC integration. Data were collected through cognitive tests and product quality assessments using structured rubrics. The findings indicate that students exposed to the integrated model demonstrated significantly higher cognitive achievement and produced furniture products of superior quality compared to those in the control group. Improvements were observed across key indicators, including finishing quality, structural strength, aesthetics, and functionality. The results suggest that embedding systematic inspection-based QC within PjBL–STEAM not only strengthens conceptual understanding but also fosters precision, quality awareness, and industry-relevant vocational skills. This study contributes to vocational education by proposing a structured integration of industrial quality inspection practices into project-based STEAM learning. The model supports the development of work-ready graduates and aligns with contemporary vocational education reforms that emphasize contextual learning, industry relevance, and 21st-century competencies.